ANALYSIS ON CLARITY AND CORRECTNESS OF GOOGLE TRANSLATE IN TRANSLATING AN INDONESIAN ARTICLE INTO ENGLISH - Tira Nur Fitria (Sanata Dharma University, 2021)
The objective of this study is to analyze the aspects of clarity and correctness in Google Translate’s ability in translating an Indonesian article from English into Indonesian. This research refers to qualitative research. Data used in this research is a published Indonesian article which is translated into English by using Google Translate. Based on the analysis, the researcher concludes that Google Translate is a machine translator, but there is always going to be potentially less clarity and correctness at the end of the translation product such as in Indonesian articles into English. Because English grammar is a complicated thing to be learned, people perhaps cannot expect more that machine translator understands every aspect of the way human beings communicate with each other. That is why the answer about the clarity and the correctness of Google Translate is that it still has a way to go before it can consistently, clearly, and correctly translate the language without errors. In the clarity aspect, there is still no clarity in English translation by Google Translate, even it translated the language word-for-word. In the correctness aspect, it refers to the mechanical rule in writing which is related to grammar, punctuation, and spelling. Some examples of non-correctness are related to grammar and punctuation errors. Machine translators have come a long way in a short amount of time, but some features still lack good translation such as in aspects of grammar and punctuation.